(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Troponin is the key biomarker for diagnosing acute myocardial infarction and plays a pivotal role in clinical cardiology. Advances in laboratory assays over the past decades have significantly improved analytical sensitivity and accuracy, enabling detection of very low troponin concentrations. Effective clinical use requires understanding both the analytical and clinical sensitivity and specificity of assays, as well as proper interpretation within the patient’s clinical context. Variability among troponin I and T tests and evolving definitions of sensitivity pose challenges for clinicians, emphasizing the need to integrate laboratory results with clinical reasoning. Enhanced understanding of troponin testing is crucial for accurate diagnosis, timely intervention, and improved cardiovascular outcomes.